2020
DOI: 10.3389/fped.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Endoscopic Pilonidal Sinus Treatment (PEPSiT) in Children With Pilonidal Sinus Disease: Tips and Tricks and New Structurated Protocol

Abstract: Background: The advent of pediatric endoscopic pilonidal sinus treatment (PEPSiT) has dramatically changed the surgical management of pilonidal sinus disease (PSD) in children and adolescents. This study aimed to report the outcome of our new structurated protocol, including PEPSiT, laser epilation, and oxygen-enriched oil-based gel dressing, for treatment of PSD in pediatric patients and describe tips and tricks of the technique. Methods: We retrospectively reviewed the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…All patients received the multi-step treatment protocol for PSD, that we have recently standardized [12][13][14]. This protocol included three steps, represented by pre-operative laser epilation therapy, surgical procedure using PEPSiT and post-operative wound management with specific dressing and laser therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received the multi-step treatment protocol for PSD, that we have recently standardized [12][13][14]. This protocol included three steps, represented by pre-operative laser epilation therapy, surgical procedure using PEPSiT and post-operative wound management with specific dressing and laser therapy.…”
Section: Methodsmentioning
confidence: 99%
“…In these 3 years of experience with the technique, we experienced some tips, tricks and technical expedients to improve the technique, that we would like to share with the pediatric surgery community [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have found that the procedure results in a lower pain experience and patients can return to work and everyday life more quickly. Another minimally invasive surgery option would be the conduction of an endoscopic treatment, which is reported to have very low recurrence and fast recovery rates (23). However, these methods may not be suitable for abscessed pilonidal sinus, recurrent PS disease and extensive findings.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of complications was categorized according to the Clavien-Dindo classification [ 9 ]. All patients were interviewed over the phone after obtaining verbal consent to confirm the recurrence status and assess their satisfaction by a single trained data collector (AHZ) through the use of the Likert scale/score assessment tool, which was utilized in multiple published papers [ 7 , 10 ]. The Strengthening The Reporting Of Cohort Studies in Surgery (STROCSS) guidelines have been followed in this project [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since there is a significant negative impact of SPND on the quality of life of affected subjects even after surgical management, new management techniques have become need of the hour, such as sinus laser therapy (SiLaT) or sinus laser-assisted closure (SiLaC). It has been evolving in the past few years with promising outcomes and reasonable patient satisfaction [ 6 , 7 ]. It is essential to know that SiLaT works by introducing a radial fiber connected to a diode laser into the sinus to eradicate its cavity after extracting the hair, and the sinus is curetted [ 5 ].…”
Section: Introductionmentioning
confidence: 99%